Effects of different supplements on Hashimoto’s thyroiditis: a systematic review and network meta-analysis - Peng, Bingcong; Wang, Weiwei; Gu, Qingling; Wang, Ping; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2024)
Clinicians often consider the use of dietary supplements to assist in lowering thyroid autoantibody titres in patients with Hashimoto's thyroiditis (HT). Currently, different supplements differ in their ability to reduce autoantibody levels. The purpose of this article is to compare the ability of different supplements to lower autoantibody titres and restore TSH levels through a systematic literature review. We obtained information from the PubMed, Web of Science, Embase, and Cochrane databases, as well as the China National Knowledge Infrastructure (CNKI). Selected studies included those using selenium, Vitamin D, Myo-inositol, and Myo-inositol in combination with selenium for the treatment of HT patients with euthyroidism. These data were combined using standardised mean differences (SMDs) and assessed using a random effects model. A total of 10 quantitative metaanalyses of case-control studies were selected for this meta-analysis. Compared to the placebo group, the use of selenium supplements was able to significantly reduce the levels of thyroid peroxidase autoantibodies (TPOAb) (SMD: -2.76, 95% CI: -4.50, -1.02) and thyroglobulin autoantibodies (TgAb) (SMD: -2.44, 95% CI: -4.19, -0.69). During a 6-month treatment, the use of Myo-inositol, Vitamin D alone, and the combination of selenium ,and Myo-inositol did not effectively reduce TPOAb